Religion og politik. Religion og integration: Afskedsforelæsning ved Københavns universitet, Det teologiske Fakultet, den 15. september 2008 - Lausten, Martin Schwarz (Kirkehistoriske Samlinger, 2009)
This Article is based on a lecture which I gave on the occasion of my retirement as Professor of Church History at the Faculty of Theology, University of Copenhagen (September 2008). It begins with some personal meditations on the study of church history during the years 1957-1965 at the University of Copenhagen. Here I refer in particular to the church historians who have inspired me most, such as the professors J. Oskar Andersen, Hal Koch, and Niels Knud Andersen. In my church history research I have emphasised history as opposed to the history of dogma, and in some instances I have succeeded to demonstrate the profits gained from focussing on manuscripts in particular. My research has - apart from the publication oftheological textbooks - been concentrated on three main areas: 1) The relationship between religion and politics in the 16th Century. That was primarily covered in my monographs on the Danish kings, Christian 2nd (1513-1523) and Christian 3rd (1536-1559), 2) The history of universities, especially in my works on the University of Copenhagen during the Middle Ages and the Reformation Era, and 3) The relationship between society and religion, particularly the role of integration, as it may be read in my six volumes (1992-2007) on the relations between Christians and Jews in Denmark from the Middle Ages to 1948.